The Efficacy of Subcutaneous Versus Oral Methotrexate in Patients with Juvenile Idiopathic Arthritis (Bangladesh Journal of Child Health, 2010)
Objective: To investigate the efficacy of subcutaneous versus oral methotrexate inpatients with Juvenile Idiopathic Arthritis (JIA) according to ACR 30 improvement criteria.Design: Prospective control trial (Parallel design) study.Setting: This study was carried out in the department of Paediatrics, BangabandhuSheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, during the periodfrom September 2006 to April 2008.Patients: A total of 40 patients participated in the study. They were divided in 2 equalgroups (Group A and Group B) alternatively matching with age, sex, and subtypes ofthe disease. Methotrexate was given orally in group A patients and subcutaneously ingroup B patients.Results: Amomg the core set variables active arthritis had the highest percentage ofimprovement in both the groups and laboratory criteria (ESR) showed lowestimprovement. According to ACR-30 criteria, improvement rate was higher in thesubcutaneous group than oral group (85% versus 65%). Side effects of MTX werealso less in subcutaneous group than oral group.Conclusion: From this study it may be concluded that the efficacy of subcutaneousMTX is more than oral MTX in JIA patients.Key words: Subcutaneous; oral; methotrexate; juvenile idiopathic arthritis.DOI: 10.3329/bjch.v33i1.5671Bangladesh Journal of Child Health 2009; Vol.33(1): 22-26